2015
DOI: 10.3390/nu7085286
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Poor Micronutrition in Family Members and Potential Risk Factors for Poor Diet in Children and Adolescents Using Korean National Health and Nutrition Examination Survey Data

Abstract: Based on data from the 2010–2011 Korean National Health and Nutrition Examination Survey, we investigated correlations between micronutrients in the diet of family members and the possible risk factors for children and adolescents consuming an inadequate diet. We examined two-generation households with children aged 2–18 years. The quality of the family diet with regard to the following nine nutrients (protein, calcium, phosphorous, iron, vitamin A, vitamin B1, vitamin B2, niacin, and vitamin C) was assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…The results of the present study indicted the DII was positively associated with parental BMI. In an extensive study carried out among Korean households, the significant correlations were observed between the pattern of vitamin intake (B 1 , B 2 , B 3 , C and A), Fe, Ca and P in parents and their offsprings ( 91 ) . In another study conducted on 294 families, the findings demonstrated the significant positive association between consumption of total carbohydrate, SFA, PUFA, energy and cholesterol in children and adolescents and their parents ( 92 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study indicted the DII was positively associated with parental BMI. In an extensive study carried out among Korean households, the significant correlations were observed between the pattern of vitamin intake (B 1 , B 2 , B 3 , C and A), Fe, Ca and P in parents and their offsprings ( 91 ) . In another study conducted on 294 families, the findings demonstrated the significant positive association between consumption of total carbohydrate, SFA, PUFA, energy and cholesterol in children and adolescents and their parents ( 92 ) .…”
Section: Discussionmentioning
confidence: 99%
“…While formative research with young adults suggests that fruit and vegetable consumption is likely to increase during the transition to parenthood ( 28 , 29 ) , if the pattern of suboptimal intake tracks into middle adulthood, it increases the risk of diet-related diseases among these adults and their offspring are likely to inherit these poor dietary patterns ( 30 ) . Thus, innovative interventions and campaigns are needed to positively influence fruit and vegetable intake of future generations of adults.…”
mentioning
confidence: 99%
“…In another extensive study carried out among 1,283 Korean households aimed to assess the correlation of some nutrients intake between family members, the findings illustrated a 0.1 ± 0.9 0.00 ± 0.9 0.0 ± 0.9 0.0 ± 0.9 0.54 TMI, kg/m 3 13.0 ± 4.1 13. 0.0 ± 0.9 − 0.9 ± 0.8 0.0 ± 0.9 0.0 ± 0.9 0.62 TMI, kg/m 3 13. positive correlation between calcium and phosphorus consumption in children/adolescents and their parents [49]. Davison et al in an observational study of 401 child-parent pairs from New Zealand demonstrated that higher parental diet quality score was associated with lower children's snack consumption [50].…”
Section: Discussionmentioning
confidence: 99%